(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Musculoskeletal pain comprises of over 200 disorders affecting muscles, joints, bones, and soft tissues which is prevalent among laptop users including students. The regular interaction of students with laptop computer interface is associated to the complex complaints relating to hand, shoulder, joints and bones. The Nigerian population aged over 50 is projected to rise by 32% between 2009 and 2030; this implies an increase in musculoskeletal disorder trend. This dissertation seeks to investigate the presence of musculoskeletal pain among the undergraduate and postgraduate laptop users of university of Abia State University, evaluate the intensity of the pain, and examine its effect on the students. The research design is a descriptive cross-sectional study conducted among 100 undergraduates from three different academic majors and 100 postgraduate students with age groups 17-40years. The data regarding details, impact, socio-demographic features, visual symptoms and sleep disorders of musculoskeletal disorders, body region of pain, and intensity of pain and laptop posture of participants were collected and analyzed using SPSS software. 193 out of 200 administered questionnaires were amenable to data analysis representing a response rate of 96.5%. The prevalence rate of MSD is 29.53% with neck pain (20.7%) as the most reported MSD complaints. The least reported body region of pain was the elbow (1.6%). The prevalence of MSD is slightly higher among the postgraduate students (15.54%) and highest among the male students aged between 26- 30 (21.54%). The intensity of the pain is high among the males than the females especially among postgraduate students; the major effect of MSD on the students as reported was absenteeism. These results indicate a low prevalence of musculoskeletal pain among students of Abia State University when compared with prevalence rates in the reviewed literature